Using cohort studies in lifecourse epidemiology - Cooper, C; Frank, J; Leyland, A; Hardy, R; Lawlor, D; Wareham, N; Dezateux, C; Inskip, H (2012)
The UK Medical Research Council (MRC) Population Health Sciences Research Network is a network of MRC research units and centres that aims to bring together and add value to existing MRC investment in public health, health services and epidemiological research. This symposium held in August 2011 at the World Congress of Epidemiology, Edinburgh, discussed a range of topics including methodology and analytical issues based on a number of examples of cohort studies within the context of lifecourse epidemiology. © 2012 The Royal Society for Public Health.